Musik Popular Bali 1950-1965 dalam Dinamika Kebudayaan Nasional - Ni Wayan Ardini; I Komang Darmayuda; Ricky Irawan (Journal of Music Science, Technology, and Industry, 2020)
Purpose: This research discusses the development of popular music in Bali and its relation to national cultural issues in the 1950-1965 period. Research methods: This research uses the theoretical framework of historical ethnomusicology and emphasizes the verstehen method to understand the meaning of music. Beside the documentary study, the collecting technique of this research uses some interviews with the musical practitioner, historian, and cultural expert. Results and discussion: Keroncong, which popular during that period, was not only an aesthetic expression in the realm of music but it is also a manifesto of Indonesianess, that they are part of Indonesian society. Implication: How to become Indonesian in the realm of music was interpreted differently in that period.